Hydrobiological Investigations on the Planktonic Diversity of Vellar River, Vellar Estuary and Portonovo Coastal Waters, South East Coast of India - C, Prabhahar. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The studies on planktonic diversity of Vellar River, Vellar estuary and Portonovo coastal waters, and South East of India were made to assess the pollution of water during the period of 2005-2006. The quantitative and qualitative evaluation of the variation in water showed that high quantity of phytoplankton population throughout the study period Euglypha sp., Brachionus sp., Brachionus calciflorus, Brachionus rubens, Euchlanis dilita, Flling longiseta, Lecane bulla, Cyclops sp., and showed the dominated group of organisms. The Vellar River through the high polluted water bodies by the direct contamination of sewage and other industrial effluents.